Perancangan Sistem Alarm Kebakaran Berbasis IoT: IoT-based fire alarm system design - Steven Yohanes Theo Pola; Fridolin Febrianto Paiki; Parma Hadi Rantelinggi (JISTECH: Journal of Information Science and Technology, 2022)
The fire rate in Indonesia is very high, the risk and impact of fire disasters is very high, from the fire department data alone, fire disasters are the most frequent disasters and are in second place after floods. the fire has been at the level of a large fire and usually after 1 or 2 houses have burned, thus making the impact of fires in residential areas even greater in terms of material and economic damage. Seeing these conditions, the author designed an IoT-based fire alarm, which is an IoT-based alarm or notification system that can notify if a fire sensor is detected by fire via the internet and by using a supporting application, namely BLYNK on a smartphone. directly the home owner and the fire department will immediately know, so that larger fires can be avoided to minimize losses. In this thesis, the researcher will explain from the initial stage to the design to the stage of testing alarm alarms based on the internet of things.